SUMEDANG UMBUL DANCE: PASEH STYLE AND SITURAJA STYLE - Nurulloh Ramdani; Tati Narawati (Universitas Pendidikan Indonesia, 2024)
The umbul dance in Sumedang was born as a traditional art that embodies the local culture of the local community. During its development process, the umbul dance experienced ups and downs caused by several factors, so that these factors resulted in changes that occurred in the Paseh and Situraja style umbul dances. This study aims to describe the structure of choreography, costume makeup, and function in the Sumedang umbul dance: Paseh Style and Situraja Style. The scientific study used in this study is ethnochoreology. The ethnochoreology study in this study is used as a theoretical umbrella based on the results sought, namely the structure of choreography, costume makeup and function in the Paseh and Situraja style umbul dances. The method used is a Qualitative method with a descriptive analysis approach. Data collection techniques used by researchers are observation, interviews, literature studies, and documentation. The results of this study found thatUmbul dance in Sumedang has several versions, namely Paseh style and Situraja style. Growing and being born in two different areas caused both to experience a development process and have similarities and differences in choreography structure, costume make-up, and function.